Prevalence of human infections caused by Fasciola hepatica in Caujul District, Oyon Province, Lima Region, Peru - Natividad Carpio, Ines S. (2018)
Introduction: Liver fasciolosis is a zoonotic parasitic disease that affects human beings. It is caused by Fasciola hepatica, and it has a great impact in public health not only in Peru but also in many areas in the world.Objectives: To determine the prevalence of Fasciola hepatica infection in Caujul District, Oyon Province, Lima Department, and to determine possible associated risk factors.Material and methods: A descriptive cross-sectional study was performed in August 2006, where 132 fecal samples from persons living in Caujul District representing every age group and comprising 37% of the total population were assessed. An anonymous survey was also administered to every participant, asking about habits and possible risk factors for acquiring Fasciola hepatica infection.Results: The prevalence of intestinal parasitoses was 95.46% in the surveyed population. However, the total prevalence of fasciolosis was 1.12%. Amongst risk factors for acquiring Fasciola hepatica infection we found the following: lack of accessibility to basic services such as water and power supply, not knowing about the presence of the disease in domestic animals, eating aquatic plants, and living in a household near the garbage dump (Fisher test: 95% confidence interval, p<0.05).Conclusions: The prevalence of Fasciola hepatica infection in Caujul District inhabitants was 1.12%, calculated for the general population of that place. Even though Caujul District may not qualify as an endemic zone for fasciolosis, we recommend having a preventive program in the area, allowing the general population, together with farmers and peasants to be informed about the different intestinal parasitic diseases affecting their community.